Sympoietic thinking and Earth System Law: The Earth, its subjects and the law - Petersmann, Marie-Catherine (Earth system governance, 2021)
This article explores what the emerging paradigm of ‘Earth System Law’ suggests in terms of reconfigurations of the Earth, its subjects and the law. Which representations of the Earth and of its subjects does Earth System Law think with? And which human-nonhuman relations do these systemic reconceptualizations translate? While innovative in many regards when contraposed to international environmental law, Earth System Law's central novelty lies in its ‘systems-oriented ontology’. Yet, it is precisely this underpinning that deserves, I argue, more critical attention. While Earth System Law's rendering of the Earth system seems to embrace an ‘autopoietic’ understanding of how life-making and life-sustaining processes are enacted, its proposed functioning of a planetary Earth System Law and the systems approach that underlies it remain elusive. This article unpacks these tenets by suggesting that, instead of looking at the functioning of the Earth through autopoietic lenses, a ‘sympoietic’ view should be preferred to make sense of how life emerges and contingently unfolds on Earth, and leave space for collective modes of being, thinking and acting in the Anthropocene.